2018
DOI: 10.1155/2018/3569493
|View full text |Cite
|
Sign up to set email alerts
|

Role of HOX Genes in Stem Cell Differentiation and Cancer

Abstract: HOX genes encode an evolutionarily conserved set of transcription factors that control how the phenotype of an organism becomes organized during development based on its genetic makeup. For example, in bilaterian-type animals, HOX genes are organized in gene clusters that encode anatomic segment identity, that is, whether the embryo will form with bilateral symmetry with a head (anterior), tail (posterior), back (dorsal), and belly (ventral). Although HOX genes are known to regulate stem cell (SC) differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
131
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 100 publications
2
131
0
1
Order By: Relevance
“…It is possible that normal tissues may not be truly normal and could have altered HOXA10 expression or there are distinct but context‐dependent roles for HOXA10 function. Aberrant and context‐dependent roles other HOX genes in the development of cancers has been observed . Further evidence for possible duplicitous roles of HOXA10 is supported by the fact that a portion of high HOXA10‐expressing PCa experienced longer time to BCR.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is possible that normal tissues may not be truly normal and could have altered HOXA10 expression or there are distinct but context‐dependent roles for HOXA10 function. Aberrant and context‐dependent roles other HOX genes in the development of cancers has been observed . Further evidence for possible duplicitous roles of HOXA10 is supported by the fact that a portion of high HOXA10‐expressing PCa experienced longer time to BCR.…”
Section: Discussionmentioning
confidence: 97%
“…Aberrant and context-dependent roles other HOX genes in the development of cancers has been observed. 34 Further evidence for possible duplicitous roles of HOXA10 is supported by the fact that a portion of high HOXA10-expressing PCa experienced longer time to BCR.…”
Section: Reduced Hoxa10 Is Observed In a Mouse Ptennull Prostate Camentioning
confidence: 99%
“…The c‐MYC gene is associated with cell proliferation, and it has been shown that the association between p53 and c‐myc may be fundamental for chemotherapy in colon carcinoma cells (Arango et al ., 2001). The SRC and HOXB3 genes are associated with proliferation, migration, and angiogenesis and may contribute to the metastatic process (Chikara et al ., 2017; Bahtlekar et al , 2018). Downregulation of the SMAD4 gene (2.85‐, 4.16‐, and 3.84‐fold downregulation for 5, 10, and 50 M, respectively) was also observed after silibinin treatment in wild‐type cells only.…”
Section: Discussionmentioning
confidence: 99%
“…In the past years, HOX genes emerged as transcriptional regulators responsible for embryogenesis and were involved in the development of various cancers . As an essential part of HOXA family genes, HOXA10 expression was crucial for ensuring normal development and differentiation of hematopoietic stem cells . Moreover, emerging evidence indicated that upregulation of HOXA10 was associated with different cancer types …”
Section: Discussionmentioning
confidence: 99%
“…4 As an essential part of HOXA family genes, HOXA10 expression was crucial for ensuring normal development and differentiation of hematopoietic stem cells. 25 Moreover, emerging evidence indicated that upregulation of HOXA10 was associated with different cancer types. 26,27 In our present study, we demonstrated that HOXA10 was elevated in GC tissues.…”
Section: Discussionmentioning
confidence: 99%